THE LEGALITY OF OWNING A GLEANINGS AFTER EXPIRATION OF THE DECLARING PERIOD - Assistant Professor Dr. Mohammed JasimNaser, L. Dr. Mohammed Hatem Jassim Al-Jawary (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The summary of our research marked (legality of owning a gleanings after the expiration of the declaring period) In it we dealt with the concept of a gleanings in language and idiom, and the whole gleanings is all the money for a Muslim exposed to being lost in the abundance of the ground and its under, and for the mandatory provisions for capturing the gleanings according to the circumstances and conditions are five: in terms of the obligation, the desirability, permissibility, hatred and prohibition, and the capture and ownership of the gleanings according to its importance and usefulness is divided into three sections: a section permissible Picking it up is owned by it, and it is the easy things that they are not interested in seeking and searching for, or that searching for it is greater than its value, and the second part: it is not permissible to pick it up and does not possess by its declaring as the stray that refrains from small lions such as the little lion, wolf and jackal. By capturing it as a gleanings of money and its meaning, it is permissible to capture it on the condition of declaring , and to indicate the most correct saying in the period of declaring of the gleanings , who said: The gleanings is known for a year, and those who said that the duration is determined according to the small and large number of the gleanings , and the weight of the last saying of it. This is because if the capture is obligated to define any sunnahgleanings , people refrain from picking up things and delivering them to their owners because the declaring requires the cost and he has to allocate a certain amount of time for that. Things that are not of great importance to their owner do not deserve all this, but he can know it. Several days, or less than that, in order to save time and money together, and what is the ruling on owning the gleanings and disposing of it after the declaring and the statement of the most correct opinion of the five sayings that if the owner defined it and did not know its owner, it became from the money of the catcher, whether the picker was rich or poor, then he guarantees it if its owner came It is like his money, and this saying has been outweighed by the power of their reasoning and they are free of slander by the investigators, as there is no distinction between rich or poor, nor between those who have loyalty or not, but rather it is general in every catcher, and if the owner comes he guarantees it for him, this and in conclusion It is an uneasy effort, and the diligence of those who see opinion today and disagree with it tomorrow.